A Torque Discontinuity Free New Hybrid PWM Approach for High Speed Induction Motor Drives. (2nd April 2014) - Rehman, Habibur; Mahmood, Roufin; Shah, Taimoor
Abstract : This paper designs a hybrid speed controller in which a Sine Triangle Pulse Width Modulated (SPWM) inverter is used below the base speed and a square wave inverter is employed above the base speed. The two inversion techniques complement each other for their advantages and disadvantages below and above the base speed. This paper proposes a unique strategy for the transition between SPWM and square wave by simply setting the frequency of the carrier signal equal to zero. The proposed methodology in a way uses only one inversion technique and realizes a seamless transition from the SPWM to square wave compared to conventional method in which modes are simply switched from SPWM to square wave and vice versa when the speed changes above and below the base speed, respectively. Computer simulations show that the proposed technique has smoother torque transition and thus a better speed response compared to conventional approach of inverter mode switching around the base speed. The performance of proposed hybrid approach is also validated on a small prototype induction motor through experimental results.